Building the library of RNA 3D nucleotide conformations using the clustering approach - Zok, Tomasz; Antczak, Maciej; Riedel, Martin; Nebel, David; Villmann, Thomas; Lukasiak, Piotr; Blazewicz, Jacek; Szachniuk, Marta (Zielona Góra: Uniwersytet Zielonogórski)
An increasing number of known RNA 3D structures contributes to the recognition of various RNA families and identification of their features. These tasks are based on an analysis of RNA conformations conducted at different levels of detail. On the other hand, the knowledge of native nucleotide conformations is crucial for structure prediction and understanding of RNA folding. However, this knowledge is stored in structural databases in a rather distributed form. Therefore, only automated methods for sampling the space of RNA structures can reveal plausible conformational representatives useful for further analysis.
Keywords: RNA nucleotides; conformer library; torsion angles; clustering; neural gas